Encyclopedia of Psychology and Religion - Leeming, David A.; Madden, Kathryn; Marlan, Stanton; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
The Encyclopedia of Psychology and Religion offers a definitive and intellectually rigorous collection of psychological interpretations of the stories, rituals, motifs, symbols, doctrines, dogmas, and experiences of the world$1 (Bs religious and mythological traditions. The Encyclopedia applies a wide range of psychological approaches to understanding the form and content of religious and spiritual experience, at the same time offering insight into the meanings of various symbols and themes of numerous religions. While there are reference works on religion and those on psychology, until now there has been no comprehensive encyclopedia that integrates psychology and religion in the context of current intellectual developments in the social/behavioral sciences. This Encyclopedia that integrates psychology and religion serves as a valuable user-friendly resource for libraries and professionals, and is of particular use to the growing community of researchers, academics, teachers, clergy, therapists, and counselors who are the real opinion leaders in the developing reintegration of religion and psychology. This Encyclopedia, interdisciplinary in approach, represents a rich new contribution to the development of human self-understanding.s
Keywords: Philosophy (General).; Philosophy; Religion (General).; Psychology -- History; Psychology; History of Psychology; Religious Studies; Philosophy of Religion